Sustainable Business Model Integration for Revenue Acceleration of Batik MSMEs in Lamongan - Mega Barokatul Fajri; Tatag Satria Praja; Khubby Mulyono; Septy Bian Sastro; Revita Dea Tri Maysahroh; Addina Haque Abdullah (Universitas Muhammadiyah Jakarta, 2026)
This study aims to analyze the acceleration of income of Lamongan batik MSMEs in Lamongan Regency using an integration method of three business analysis models, namely the Value Chain analysis model, Business Model Canvas, and PESTEL analysis. This is to create a sustainable business model. This research is a descriptive qualitative study with the research objects being the Chotifa Batik MSME in Sendang Duwur Village and the Bani Yasit Batik MSME in Sendang Agung Village. The results show that the combination of the three sustainable business models can provide a detailed and comprehensive overview of the internal and external conditions of Lamongan batik MSMEs. The value chain analysis shows that both Lamongan Batik MSMEs, namely Batik Chotifah and Batik Bani Yasit, have weaknesses in terms of raw material procurement and technology in the production process. The PESTEL analysis shows that economic, technological, and environmental factors are issues that must be prioritized. BMC analysis shows that Batik Chotifa focuses on the lower-middle segment with expertise in natural dyeing. Meanwhile, Batik Bani Yasit focuses on the upper-middle segment with innovative batik designs. The integration of these three models makes it easier for Batik MSMEs to categorize the external challenges they will face, optimize internal activities, and develop effective, efficient, adaptive, and sustainable business strategies. By integrating a sustainable business model, Lamongan Batik MSMEs have the opportunity to increase their competitiveness, expand their market to the global market, and preserve local culture and the surrounding environment